2021
DOI: 10.1002/jso.26412
|View full text |Cite
|
Sign up to set email alerts
|

Current state of minimally invasive pancreatic surgery

Abstract: The growth in minimally invasive pancreatic surgery (MIPS) has been accompanied by a recent surge in evidence‐based data available to analyze patient outcomes. A small complement of randomized control trials as well as a multitude of observational studies have demonstrated both consistent similarities and differences between MIPS and the open approach, although abundant questions remain. This review highlights the available literature and emphasizes key factors for evaluating laparoscopic and robotic pancreati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Indeed, it has been reported that only 4-14% of the PDs performed in the United States over the last two decades, were carried out with a minimally invasive approach. This could be due to the high complexity of minimally invasive PDs, especially if performed with traditional laparoscopy [24]. Nevertheless, in the last years, RAS has been increasingly diffused for different surgical procedures, including pancreatic surgery, mostly for distal pancreatectomy but also for PD.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been reported that only 4-14% of the PDs performed in the United States over the last two decades, were carried out with a minimally invasive approach. This could be due to the high complexity of minimally invasive PDs, especially if performed with traditional laparoscopy [24]. Nevertheless, in the last years, RAS has been increasingly diffused for different surgical procedures, including pancreatic surgery, mostly for distal pancreatectomy but also for PD.…”
Section: Discussionmentioning
confidence: 99%
“…A number of observational studies and several metaanalyses have suggested comparable rates of overall morbidity and postoperative pancreatic fistula (POPF) between conventional laparoscopic and robotic pancreatectomy, including both distal resection and pancreaticoduodenectomy. [1][2][3][4][5] At the same time, the available data from large studies comparing the two approaches with propensity score matching show that robotic surgery is consistently associated with lower rate of unplanned conversion to an open procedure and higher proportion of spleen preservation in the case of distal pancreatectomy performed for benign and borderline conditions. [2][3][4] Actually, compared with standard laparoscopy, the robot may offer significant benefits in terms of visualization, exposure, and surgical dexterity in dissecting and suturing, 1,3-5 making the robotic approach particularly well suited for technically challenging pancreatectomies, such as that we recently reported for the treatment of multifocal involvement of the pancreas by melanoma metastases.…”
Section: Presentmentioning
confidence: 99%
“…In the absence of randomized evidence on this topic, it is still difficult to draw definitive conclusions to support one technique over the other. 1 Furthermore, when comparing robotic with laparoscopic surgery, several indirect aspects should be taken into account, including the impact of the specific learning curve required for any given procedure. [2][3][4]6 In fact, most surgical teams dedicated to pancreatic MIS have robust experience either in laparoscopic or in robotic surgery, which significantly limits the possibility of running reliable head-to-head comparisons.…”
Section: Futurementioning
confidence: 99%
See 2 more Smart Citations